Degrowth and Capitalist Power: A Step Towards a Theory of Change - Julien Vastenaekels (Degrowth Journal, 2024)
This article explores the relationship between degrowth and the theory of Capital as Power (CasP), aiming to understand how socio-ecological transformations can unfold against capitalist power dynamics. While degrowth scholars have largely overlooked this perspective on capital, CasP argues that capitalism is primarily a mode of power, with capitalisation quantifying power – the confidence in in – the ability to shape society against opposition. Key CasP concepts are brought into dialogue with degrowth research to identify potential implications and offer a step towards a theory of change for degrowth. The article first outlines the CasP perspective, including its notion of power, the process of capitalisation and the conflictual nature of capital accumulation, and highlights links with degrowth research. It then looks at the elements underlying the valuation of capital as power and how they provide entry points for degrowth transformations. The role of dominant capital groups and the concept of “sabotage” in exercising power over society are then addressed. As such, degrowth transformations must challenge the confidence of dominant capital groups in their ability to rule, as these groups inhibit possibilities for socio-ecological change. This dynamic, summarised in a conceptual diagram, provides a first step towards a theory of change for degrowth in the face of capital accumulation. Finally, the conclusion offers potential directions for further research.
Keywords: P; P1; P18; Q5; O4; 330; capitalism; accumulation; degrowth; ecology; power; sabotage; socio-economic transition